2022
DOI: 10.1093/mnras/stac2238
|View full text |Cite
|
Sign up to set email alerts
|

Probing the z ≳ 6 quasars in a universe with IllustrisTNG physics: impact of gas-based black hole seeding models

Abstract: We explore implications of a range of black hole (BH) seeding prescriptions on the formation of the brightest z ≳ 6 quasars in cosmological hydrodynamic simulations. The underlying galaxy formation model is the same as in the IllustrisTNG simulations. Using constrained initial conditions, we study the growth of BHs in rare overdense regions (forming ≳ 1012 M⊙/h haloes by z = 7) using a  (9 Mpc/h)3 simulated volume. BH growth is maximal within haloes that are compact and have a low tidal field. For these haloes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 148 publications
1
8
0
Order By: Relevance
“…In this case, NDCBH reaches unity at a halo mass of ∼ 10 9 M . With this threshold halo mass, cosmological simulations showed that the formation of high-z quasars can be explained (e.g., Bhowmick et al 2022). This supports our estimate of minimum halo mass for DCBH formation.…”
Section: Occupation Fraction At Z = 10supporting
confidence: 85%
See 2 more Smart Citations
“…In this case, NDCBH reaches unity at a halo mass of ∼ 10 9 M . With this threshold halo mass, cosmological simulations showed that the formation of high-z quasars can be explained (e.g., Bhowmick et al 2022). This supports our estimate of minimum halo mass for DCBH formation.…”
Section: Occupation Fraction At Z = 10supporting
confidence: 85%
“…For halos with masses 10 9 -10 10 M , NDCBH exceeds unity, meaning that on average they can host multiple DCBHs. However, those DCBHs may experience merger with each other along the merger tree when progenitors that host DCBHs merge with another progenitor or the main halo (Chen et al 2022;Bhowmick et al 2022). As we do not consider the merger of DCBHs in this study, the value shown in Fig.…”
Section: Occupation Fraction At Z = 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these semi-analytical models and cosmological simulations could reproduce the mass of GN-z11 at z = 10.6 (refs. 7 , 25 27 ). The solid and dashed lines show the evolutionary tracks for some of them (described more extensively in the Methods ).…”
Section: Mainmentioning
confidence: 99%
“…To determine the initial conditions of the early BH assembly, the formation pathway of seed BHs has been extensively investigated by numerical simulations and semianalytical studies (Begelman et al 2006;Regan & Haehnelt 2009;Tanaka & Haiman 2009;Natarajan & Volonteri 2012;Hirano et al 2014Hirano et al , 2015Valiante et al 2018;Sassano et al 2021;Bhowmick et al 2022;Toyouchi et al 2023). Massive star formation episodes in the early universe are substantially modulated by external environmental effects such as (i) H 2 photodissociating irradiation from nearby galaxies (Omukai 2001;Oh & Haiman 2002;Bromm & Loeb 2003;Shang et al 2010;Sugimura et al 2014;Visbal et al 2014;Chon et al 2016), (ii) supersonic baryonic streaming motion that delays gas collapse in halos (Fialkov et al 2012;Tanaka & Li 2014;Schauer et al 2017;Hirano et al 2018;Inayoshi et al 2018), and (iii) dynamical heating caused by frequent halo mergers and turbulence injection led by cold accretion flows (Yoshida et al 2003;Mayer et al 2010Mayer et al , 2015Wise et al 2019;Latif et al 2022).…”
Section: Introductionmentioning
confidence: 99%